2015
DOI: 10.1073/pnas.1502545112
|View full text |Cite
|
Sign up to set email alerts
|

Combining paleo-data and modern exclosure experiments to assess the impact of megafauna extinctions on woody vegetation

Abstract: Until recently in Earth history, very large herbivores (mammoths, ground sloths, diprotodons, and many others) occurred in most of the World's terrestrial ecosystems, but the majority have gone extinct as part of the late-Quaternary extinctions. How has this large-scale removal of large herbivores affected landscape structure and ecosystem functioning? In this review, we combine paleo-data with information from modern exclosure experiments to assess the impact of large herbivores (and their disappearance) on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
308
1
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 323 publications
(328 citation statements)
references
References 121 publications
(152 reference statements)
11
308
1
8
Order By: Relevance
“…A range of tools have been applied to tackle this topic, including ecological observations and experimental manipulations in the remaining megafauna-rich regions (18,49). The impacts of past extinctions have also been explored through paleoecological studies using pollen grains, charcoal particles, and beetle communities as indicators of ecosystem structure (14).…”
Section: Megafauna Prehistorymentioning
confidence: 99%
See 3 more Smart Citations
“…A range of tools have been applied to tackle this topic, including ecological observations and experimental manipulations in the remaining megafauna-rich regions (18,49). The impacts of past extinctions have also been explored through paleoecological studies using pollen grains, charcoal particles, and beetle communities as indicators of ecosystem structure (14).…”
Section: Megafauna Prehistorymentioning
confidence: 99%
“…The most immediate and direct environmental effect of terrestrial megafauna is on the physical structure of ecosystems. Bakker et al (18) review the various ways in which megafauna shape ecosystem structure. Megafaunal browsers, and proboscideans in particular, are shapers of habitat structure through destruction of vegetation, through either their high rates of consumption or through breakage and trampling, and also by reducing productivity through damage to plants.…”
Section: Key Impacts Of Megafaunal Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…He argued that increased forest cover from the last glacial to interglacial conditions was partly the result of extinction of the Pleistocene fauna (13). Many experimental and observational studies have shown that mammals have the capacity to create open ecosystems by reducing tree biomass whether in the tropics or temperate and boreal regions (14,15). Although Owen-Smith (13) emphasized megaherbivores (animals >1,000 kg) as primarily responsible for open habitats, mesobrowsers (4-450 kg), such as deer, antelope, and caprids, are very effective at preventing woody plants from escaping the "browse trap" and growing into larger size classes.…”
mentioning
confidence: 99%